Influência da silanização de pinos de fibra de vidro na resistência de união a um cimento resinoso autoadesivo - SANTOS, Lairds Rodrigues dos (2016)
The purpose of this in vitro study was to evaluate the influence of different chemical and mechanical surface treatments alone or in association with the silane, on GFPs bond strength using a self-adhesive resin cement. Eighty-four unirradicular bovine roots divided into six groups (n = 14) were prepared and submitted to bond strength analysis after cementation with fiber glass posts (GFPs). The following surface treatments were evaluated: control (C) - without surface treatment, silane (S), 24% hydrogen peroxide for 1 minute (PER), 24% hydrogen peroxide for 1 minute with silane (PER + SIL) , blasting with aluminum oxide particles 50μm (JAT) and blasting with 50μm aluminum oxide particles with silane (JAT + SIL). Then, the experimental groups received application of the adhesive layer and were cemented using a self-adhesive resin cement U200. A layer of composite resin was inserted over the cervical surface of the roots. After 7 days of storage in distilled water at 37ºC, the roots were submitted to serial cuts, perpendicular to the long axis of the pin, obtaining two slices for each third (cervical, middle, apical) with dimensions of approximately 1.4mm. The samples were submitted to the mechanical Push-out test on the Instron 3342 machine at a speed of 0.5mm / min, operating with a 500 N cell-load in the apico-cervical direction until the specimens were ruptured. For an analysis of the RU the data were submitted individually to the analysis of variance in a single factor, being the factor under study or surface treatment, followed by the TUKEY test that was applied for comparisons between the groups. The results demonstrated that there was a statistically significant difference in the interaction between the six groups (p <0.001). The groups (SIL: 10.5 ± 3.5MPa, JAT + SIL: 11.5 ± 3.2MPa, PER + SIL: 11.6 ± 4.6MPa) presented the highest values of RU in comparison to the groups (Control: 6.5 ± 2.9 Mpa, JAT: 8.6 ± 4.0 Mpa, PER: 7.1 ± 2.8 MPa), there was no statistically significant difference between the groups receiving silanization. The fracture mode varied according to the surface treatment used in cement-dentin and cement-pine. The groups SIL, JAT, PER + SIL presented higher frequency of cement-pin adhesive failure, while the groups Controle, JAT + SIL and PER groups showed a higher percentage of cement-dentine adhesive failures. It was concluded that the use of silane influenced the increase in bond strength.